KONFLIK TENURIAL PADA HUTAN LINDUNG GUNUNG SIRIMAU WILAYAH KPHL UNIT XIV KOTA AMBON - Sylvia Sitania; Agustinus Kastanya; Marthina. Tjoa (Program Studi Manajemen Hutan, Pascasarjana Universitas Pattimura, 2020)
Tenure conflicts are usually caused by unclear rights (laws / regulations / regulations) related to the administration of the tenure system. This study aims to identify land tenure rights of indigenous communities in the area of KPHL Unit XIV Ambon City. A qualitative descriptive approach was used in this study, using the RaTA (Rapid Land Tenure Assessment) analysis. Potential conflicts in the form of evidence of de jure and de facto claims by the parties over land and natural resource tenure systems are very evident between the customary community and the UPTD KPHL Unit XIV Ambon City.